What makes strategic decisions different : you have to know what kind of decision you're making in order to make it well - Rosenzweig, Phil (2013)
States that the right approach to successful decision making depends on how much control the decision maker has over terms outcomes, and on whether sucess will be judged in relative or absolute terms. Adds that managers will make better strategic decisions when they learn to identify which kind they are facing and develop the versatility to change approaches accordingly.